Peranan Negara dalam Pembangunan Perbandingan antara Kebijakan Pemerintahan Orde Baru dengan Pemerintahan Orde Reformasi - 1 (Universitas Dr. Soetomo Surabaya, 2018)
Development is an activity process that aims to create a more advanced society and social life. Because the scope of development touches the various areas of human life, then the range to be achieved by itself summarizes many aspects, both aspects of social politics, socioeconomic, socio-cultural and defense and security issues In general, development is done in developing countries whether it seca physical, non-physical, material or immateril. Similarly, the Republic of Indonesia, from a new independence until the age of more than 70 years of republic has experienced three times the political system of government, namely the Old Order, the New Order and the Reform Order.This article attempts to elaborate a small comparison between the New Order and the Reform Order on its policies and approaches to development. The policies adopted by the New Order government were applied in two general strategies: economic strategy and political strategy.The concept used to distinguish the two order development is state centered and statism. State centered in the New Order is clarified in three different approaches: politics as commander, economy as commander and morality as commander. While the concept of statism seen in various policies with absolute properties, both on the needs of primary, secondary and tertiary. Nevertheless everything is in stable situations and conditions, although in the end the condition is false and everything is messy.In contrast to the Reform Order, all governments of the four presidents put more emphasis on democracy in various fields, whereas the concept of state centered and statism was less emphasized so that the situation and condition of primary, secondary and tertiary needs happened more leads to instability.